Investigating Students’ Peer Feedback of Essay Writing on Google Docs - Puspita, Nurul; A. Hasyim, Umar Alfaruq (Universitas Islam Negeri Raden Intan Lampung, 2023)
Google Docs, integrated into the Google suite, is a sophisticated word processing tool surpassing Microsoft Word. This study explores peer feedback activities within Google Docs during the writing stage, emphasizing its significance. The qualitative research involves document analysis and observation to portray students' engagement in peer feedback. Findings reveal a paperless process using a peer feedback checklist, promoting students' self-reflection. This underscores Google Docs' effectiveness for facilitating online peer feedback